Size-dependent ligand exchange of colloidal CdSe nanocrystals with S2− ions. Issue 110 (22nd October 2015) - Liu, Limin; Zhang, Xianfeng; Ji, Li; Li, Hanwen; Yu, Huijuan; Xu, Fangjie; Hu, Jianhua; Yang, Dong; Dong, Angang
Abstract : An unexpected, size-dependent photoluminescence brightening phenomenon is observed during S 2− treatment of colloidal CdSe nanocrystals. Abstract : In the surface treatment of colloidal nanocrystals (NCs), S 2− ions have been widely employed as metal-free atomic ligands to efficiently replace the original long hydrocarbon ligands. Prior studies exclusively show that S 2− ions considerably quench the photoluminescence (PL) of semiconductor NCs ( e.g., CdSe and PbS) during ligand exchange. Here we report that the influence of S 2− treatment on the luminescent properties of CdSe NCs is highly dependent on the NC size. We observe an unexpected PL brightening phenomenon when small CdSe NCs (<4 nm) are subject to S 2− treatment followed by incubation in the presence of air and light irradiation, whereas PL enhancement is not observed in large CdSe NCs (>4 nm) treated under the same conditions. Systematic characterization establishes the evolution of CdSe/CdS core–shell structures in small CdSe NCs arising from anion exchange between Se 2− and S 2−, which in conjunction with the subsequent incubation process accounts for the PL enhancement. Notably, 2.1 nm CdSe NCs treated with (NH4 )2 S exhibit a PL quantum yield (QY) as high as ∼40% after 2 days of incubation, which is comparable to that of conventional hydrophobic CdSe/CdS core–shell NCs synthesized at high temperatures. Our studies demonstrate that S 2− ions can substantially substitute Se 2− in small CdSe NCs in addition to replacing the surface-coating ligands, enabling highly luminescent, hydrophilic CdSe/CdS core–shell NCs at room temperature.